Outdoor Camping Effectiveness Through Hizbul Wathan's Scouting Movement In Student Leadership : Efektivitas Outdoor Camping Melalui Gerakan Pramuka Hizbul Wathan Dalam Kepemimpinan Mahasiswa - Badiya Izza; Istikomah (Academia Open, 2021)
The outdoor camping effectiveness through the Hizbul Wathan scouting movement in ormawa Umisda to know the outdoor application of camping through the Hizbul Wathan scouting movement in creating leadership character; and outdoor camping effectiveness through Hizbul Wathan's leadership leadership movements. The method used is a descriptive qualitative method using observation, interview, and doctoring methods. Outdoor camping operations in Hizbul Wathan divide into 7 stages, among others: (a) preparation, (b) organizers, (c) events, (d) implementation, (e) completion, (f) evaluation, and (g) records. Research shows the formation of a student leadership character integrated into islamic values and application of a code of honor/promises and hizbul wathan guidelines that includes attitudes: (a) honest, (b) responsible, (c) self-contained, (d) discipline, (f) tolerance, (h) religious, (h) caring. Keyword: outdoor camping, leadership character, Hizbul Wathan